Floristic diversity of cereal fields conducted under a pivot center in the Ouargla region (case of the cereal perimeters of Hassi Ben Abdallah) - SAYED, Ibtissem (International Journal of Sciences and Natural Ressources, 2022)
The characterization of the messicole flora of the cereal fields conducted under center pivots in the region of Ouargla was carried out from 96 floristic records in experimental plots distributed over the entire surface of the different pivots chosen for our experimentation and this throughout. The phenological development cycle of the planted crop. The total weed flora inventoried includes 52 species classified into botanical families, classes, biological groups and origins. The composition of the weeds is characterized by the dominance of the introduced messicoles, compared to the spontaneous species, provided essentially by the Poaceae (monocotyledons), botanical family and class characteristic par excellence of the weed flora of our study region. There is also a dominance of Asteraceae and Brassicaceae botanical families in disturbed environments. Therophytes were par excellence the most contributory species to the specific richness of the weed flora of the study region.